Economic and Environmental Impacts of Cropping Pattern Elements Using Systems Dynamics - Masoumeh Hashemi; Hamed Mazandarani Zadeh; Peyman Daneshkare Arasteh; Mehdi Zarghami (Civil Engineering Journal, 2019)
Tragedies arising from poor water resources management and planning are significantly more relevant than climate change and frequent natural droughts, especially in arid and semi-arid areas. Nearly 92% of total water is allocated to the agricultural sector in Iran. In this situation, cultivation patterns play an important role in agricultural water management. Evaluating the effect of each crop would help the stakeholders make a rational decision in choosing appropriate cropping patterns to avoid groundwater depletion as well as maintain their livelihoods. The Qazvin plain in Iran, whose aquifer has had a drawdown of nearly 20m during the last 15 years, was used in this case study. It has been modeled using system dynamics, which includes two subsystems: hydrology, for calculating groundwater level, and economy, for defining farmer’s income in the years from 1997 to 2011. The system dynamics, which included 17 crops, was developed after calibration by simple genetic algorithm and verification under extreme condition tests. To identify the economic and environmental effect of each of the crops, the system dynamics was run 18 times, removing crops one by one. It has been found that wheat plays an important role in causing a negative water balance but does not affect the farmers’ incomes as significantly as grapes. Two indicators, which included sustainable water resources and water exploitation, were employed to assess the scenarios as well. According to the results, no scenarios are fully sustainable for maintaining a steady aquifer, but scenario 1, which removed wheat from the cropping pattern, is the most sustainable and puts the least pressure on the aquifer.